Renewal of companies: Industry switching as a form of structural change - Natalia Kuosmanen; Timo Kuosmanen; Jyrki Ali-Yrkkö; Mika Pajarinen (The Research Institute of the Finnish Economy (ETLA), 2022)
The contributions of entry and exit of firms to aggregate productivity growth are well-established in the literature. However, the impact of industry switching of firms on productivity remains overlooked. The purpose of this report is to shed new light on the role of industry switching as a form of structural change. The results show that industry switching is very common and occurs in all industries in Finland, especially during the times of recession. Industry switching has had both positive and negative contributions to aggregate productivity in different periods. Intra-industry switching had mainly negative impact on productivity growth suggesting that switching was taken as a strategy to survive. On the other hand, inter-industry switching had mainly positive impact on productivity growth, suggesting that switching was associated with new products and technologies. The study also looked at the structural developments of industries relevant for combating climate change. As emission reduction targets require companies to renew their product and service offerings, climate policy can help guide companies to switch industries. However, in the industries examined in the study, restructuring has so far taken place mainly through entry and exit.
Keywords: C81; D22; L16; 330; Industrial structure; Industry switching; Labor productivity; Productivity decompositions